Plucna funcija rukometasa razlitchnih dobnih kategori - Foretic, N.; Uljevic, O.; Rogulj, N.; Marinovic, M. (Croatian Sports Medicine Journal, 2013)
This investigation was conducted on 85 handball players, 35 seniors, 29 juniors and 21 cadets, with the aim of defining their pulmonary function and determining the difference between the groups, if any. Following parameters of pulmonary function and anthropometry were measured: VC, FEV1, MEF50, MEF25, PEF, body height, body weight. Respondents reported a chronological age and the status of tobacco smoke exposure. T-test for independent samples revealed differences in spirometry and anthropometric parameters. Anthropometric differences between groups were significant and defined by the structure and demand of handball game in different age categories. Vital capacity was significantly higher for seniors than for juniors and cadets. Juniors achieved significantly better results in variables FEV1 and PEF (highly correlated) than the other groups. The differences between seniors and cadets are not significant. This is explained with poorer status of anaerobic energy components in senior respondents. Variables for assessment of small airways showed significantly lower scores for senior respondents than in the cadets and juniors. T-test showed that the senior respondents are significantly more exposed to tobacco smoke. It has greatest negative impact in the variables MEF50 and MEF25. Differences in pulmonary function between different age categories of handball players are conditioned by the structure of a sport, anthropometric characteristics, training methods and lifestyle.